Sustainable tourism development from the perspective of digital communication - Fianto, Achmad Yanu Alif; Andrianto, Novan (Faculty of Communications Science, Dr. Soetomo University, 2022)
Tourism-related enterprises around the globe are shifting more towards environmentally friendly services. This research provides a theoretical discussion and aims to assess the continuous digital communication activities of tourism business players tiny and medium-scale companies and give an overview of their existence in digital communication technology. This research focuses on determining the concept and various sustainable performance indicators. The data were collected directly from official websites, accommodation booking applications, and social media. This research adopts a matrix dimension to build a database and analyse the meaning of words in the relationship between meeting visitor needs, service quality, cultural wealth, community welfare, and resource efficiency. The research uses the Partial Least Square-Structural Equation Model (PLS-SEM) approach to test the model that has never been stretched and grouped using heterogeneous techniques. The findings revealed that foreign credentials were less adaptable for local credentials than one-off credentials and that fewer enterprises rate eco-labels on online advertising. The rate of participation of society on the platform was seen to be more complex and intellectual. This research is one of the first to investigate the resilience mechanism in the tourism industry firms. It is anticipated that this research would encourage more studies on the principle of contact and the quality of SME strategies in hospitality and contribute to the drive to facilitate broader acceptance of managerial implications.